Instalación y manejo agronómico de los clones mejorados ‘inia 321 kawsay’ e ‘inia 325 poderosa’ de solanum tuberosum l. en Pataz, La Libertad - Carrera Paredes, Walter (2017)
The present paper describes planting and crop care of breeded native andean potato clones 'INIA 321 Kawsay' and 'INIA 325 Poderosa' in Suyubamba annexed, Pataz district and Alacoto annexed, Piás district; both districts located in the province of Pataz, La Libertad. The data for information came up from training farmers on basic seed production and agronomic potato management as a strategy to disseminate the new breeded native clones through the participation of farmers in the management of demonstratives plots. The main agricultural practices were field ploughing with previous yacht liming distribution, furrowing at 1 m of distance, sowing seed potatoes at 0.20 cm distance between blows achieving 50,000 plants.ha-1. In the plot of Suyubamba, to the moment of the sowing it was applied 10,650 kg of chicken manure, 241 kg of phosphate diamónico, 139 kg of chloride of potassium and 147 kg of urea. In the plot of Alacoto, to the moment of the sowing it was applied, 10,300 kg of chicken manure, 198 kg of phosphate diamónico, 123 kg of chloride of potassium and 108 kg of urea. Diabrotica sp and Epitrix sp, were present at mild level, as far as Phytophthora infestans disease presented insignificant damages, instead Rhizoctonia solani was absent for 'INIA 321 Kawsay' in Alacoto. Sanitation control, in all cases, was chemical. Harvest time was 5 months after sowing. Breeded clone 'INIA 325 Poderosa' yielded 10.14 t.ha-1 in Suyubamba annexed and 17.0 t.ha-1 in Alacoto annexed. 'INIA 321 Kawsay' yielded 13.96 t.ha-1 in the annex of Suyubamba and 14.29 t.ha-1 in the annex of Alacoto.